The "Big Survey": Decolonisation, Development and the First Wave of NGO Expansion in Africa After 1945. Issue 4 (6th September 2022) - Cullen, Poppy; McCorriston, Steve; Thompson, Andrew
Abstract: This article sheds new light on NGO activity across Africa after the Second World War and the vital yet overlooked role played by non-state actors in the process of decolonisation. The International Council of Voluntary Agencies' 'Repertory of Africa's NGOs' (1968), analysed here for the first time, yields unprecedented insights into the 'first wave' of NGO expansion as an important aspect of the history of twentieth century international relations. We situate ICVA's Repertory in the spate of 'Big Surveys' which questioned development policy and practice. We then examine the link between decolonisation and NGO expansion and evolution. Decolonisation was a global phenomenon, involving a wide array of non-state actors intent upon shaping the post-colonial world. The Repertory provides a stronger basis for the view that ex-colonial powers expected to retain close links with former colonies and colonial connections were replicated through NGO activities. Global history is not only a matter of empire, however. We further reveal how, already by the later 1960s, territorial pathways forged by colonialism were disrupted by international NGOs from countries with no history of imperialism in Africa, and how an expanding footprint of indigenous NGOs gave Africans the means to assert agency over development agendas and take back vital aspects of their own governance amidst 'second wave decolonisation'.